Bipolar disorder and Lewy body dementia: case report and literature review - Nakamura, Sayuri; Sugawara, Hiroko; Asada, Ryo; Hatanaka, Akito; Hori, Hikaru (Frontiers in Psychiatry, 2024)
Depressive episodes with psychotic symptoms are prevalent among the older adults, emphasizing the need to differentiate them from dementia with Lewy bodies (DLB), in which depressive and psychotic symptoms commonly coexist. In contrast, psychotic symptoms occur more frequently in depressive episodes of bipolar disorder (BD) than in major depressive disorder (MDD). Although MDD is a significant risk factor for dementia, studies exploring the relationship between BD and dementia are lacking. This report details the case of a 74-year-old female who experienced severe psychotic depression that led to suicide attempts during a long-term course of young-onset BD. Ultimately, she was diagnosed with DLB based on her neurocognitive symptoms and results of the neuroimaging examination. She had experienced multiple relapses in the past, predominantly characterized by depressive episodes in her old age. Notably, she had never undergone lithium treatment, which is known for its potential efficacy in preventing relapse and dementia. Recent systematic reviews and meta-analyses have suggested that patients with BD have a higher risk of dementia than the general population, and that lithium usage is associated with a reduced risk. Moreover, patients with BD have been suggested to have an elevated risk of developing Parkinson's disease (PD), and the pathophysiological relationship between BD and PD may be attributed to dopamine dysregulation resulting from multiple relapses. Future research is imperative to identify strategies for preventing dementia in patients with BD and to develop interventions for the comorbidities of BD and DLB.